MENYINGKAP NARASI DEKONSTRUKSI DALAM NOVEL CALA IBI (BERHALUSINASI TENTANG SEBUAH HALUSINASI) - Hetty Purnamasari; Triyana Andra Nugraha (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
The novel Cala Ibi tells about the dream Maya has. In short, the story in Maya's dream is multi-layered and is one entity. Therefore Maya must find the meaning of these dreams. In her novel Cala Ibi, Nukila Amal tries to disconstruct a fixed structure of a novel that is understood by the readers. The structure of plot, the choice of characters, characterization, and the choice off setting are almost all deviated from the position of the elements of a novel. From the beginning, the narrator has decided not to obey the structure of a novel. The indication of her trying to disconstruct the novel’s structure happens to almost all of the parts of the novel. Nevertheless, the meaning given to the readers is an interesting challenge. This novel is examined with a deconstruction approach that aims to describe how the deconstruction is displayed in the novel Cala Ibi. Deconstruction is done by giving attention to symptoms that are hidden, deliberately hidden, such as untruth, side characters, women, and so on.